Sustainability Practices And Corporate Performance: A Global Perspective - M Mukhbir (PT. Gudang Pustaka Cendekia, 2025)
This study examines the relationship between sustainability practices and corporate performance in the global context. In an era of rapid technological advancements and heightened environmental awareness, companies are increasingly integrating sustainability strategies, such as Corporate Social Responsibility (CSR), environmental management, and sustainable financial policies, into their operations. The research identifies the main issues faced by businesses in implementing these practices and explores the impact of sustainability on both financial and non-financial performance. The findings indicate that companies adopting sustainability practices show improvements in profitability, efficiency, customer loyalty, and employee satisfaction. For instance, companies in sectors such as energy and manufacturing experienced a notable increase in Return on Assets (ROA) and Return on Equity (ROE) after integrating sustainability efforts. Furthermore, the study highlights the significant role of external factors such as government policies and corporate culture in the success of sustainability initiatives. The results contribute to the understanding of how businesses can leverage sustainability to achieve competitive advantage while addressing environmental and social challenges.